Genomic and epigenomic heterogeneity in chronic lymphocytic leukemia - Guièze, Romain (Blood, 2015)
Defining features of chronic lymphocytic leukemia (CLL) are not only its immunophenotype of CD19(+)CD5(+)CD23(+)sIg(dim) expressing clonal mature B cells but also its highly variable clinical course. In recent years, advances in massively parallel sequencing technologies have led to rapid progress in our understanding of the CLL genome and epigenome. Overall, these studies have clearly demarcated not only the vast degree of genetic and epigenetic heterogeneity among individuals with CLL but also even within individual patient leukemias. We herein review the rapidly growing series of studies assessing the genetic and epigenetic features of CLL within clinically defined periods of its growth. These studies strongly suggest an evolving spectrum of lesions over time and that these features may have clinical impact.